Design Of Document Information System And Monitoring Of Regional Financial Report Quality - Sofa, Aulia Rizka; Putri, Nasywa; Azzahra, Fathonah; Faracty, Cilciva Ajeng Gita; Irawan (CV Raskha Media Group, 2025)
This study aims to design and analyze a document information and monitoring system that plays a role in improving the quality of regional financial reports. The document information system is designed to manage financial archives digitally for easy access, security, and integration, while the monitoring feature functions to monitor the report preparation process in real time to ensure timeliness and data accuracy. The method used is a conceptual-descriptive approach, namely by reviewing literature, government regulations, and previous research related to government information systems and public financial reporting. The results of the analysis show that the implementation of a document information and monitoring system can strengthen the relevance, reliability, comparability, and ease of understanding of financial reports, as stipulated in the Government Accounting Standards (SAP). This system also supports increased efficiency, transparency, and accountability of regional financial management through digital recording and automated audit trails. Thus, the development of this information system is expected to encourage the creation of more modern, effective, and accountable regional financial governance.